Damage Characteristics of Polymer Plates under the Impact of the Near-Field and Contact Underwater Explosion. (7th July 2021) - Liu, Shucan; Zhao, Xiaohua; Fang, Hongyuan; Du, Xueming; Xue, Binghan
Abstract : In order to study the damage characteristics of polymer plates under the impact of the underwater explosion, the underwater contact and near-field explosion tests of polymer plates were conducted using different explosive quantities. In this paper, eight polymer plates with the size of 500 mm × 500 mm × 60 mm were made, and eight groups of explosion tests were carried out by using the rock emulsion explosive and nonconductive detonators. The damage modes and spatial distribution characteristics of the polymer plate generated by the underwater contact and near-field explosion impact with different explosive quantities are compared and analyzed. In addition, the characteristics of the shock wave propagation in the plates are investigated. It can be observed that the main damage mode of polymer plate is overall damage under the contact underwater explosion. For the near-field explosion, the main damage mode changes to overall failure, and the damage of contact explosion to polymer plate is greater than that of underwater near-field explosion. The polymer plate can reduce and delay the shock wave effectively, but the effect decreases with the increase of explosive quantity in the underwater contact explosion.